REVIEW OF SURGICAL TREATMENT METHODS WHICH ARE USED IN OBSTRUCTNE EXTRAHEPATIC ICTERS - A. Hakan DEMIREL; A. Rıza ÖZTOPRAK; Buğra KAPTANOĞLU; Ayhan KESKİN and A. Ulvi ÖNGEREN (Turkish Journal of Gastroenterology, 2020)
-